DEVELOPMENT OF DAC INDIRECT ELISA FOR THE RAPID DETECTION OF COCONUT ROOT (WILT) DISEASE - M.Sasikala; K.R.Chithra; J.J.Solomon; G.Rajeev (International Coconut Community, 2001)
Identification of root(wilt) disease-free palm is a basic requirement for evolving disease resistant/tolerant planting materials for the management of this phytoplasma induced malady. For this purpose, various types of ELISA were performed with different enzymes and their respective substrates to standardize the most suitable and sensitive one. Indirect ELISA, Protein A indirect ELISA and F(ab')2 indirect ELISA using Alkaline Phosphatase conjugate and DAC indirect ELISA using Horse raddish peroxidase conjugate were carried out. Of the various types of ELISA tried, DAC indirect ELISA has been found to be the best for the rapid detection of coconut root(wilt) disease. In this assay, crude leaf extracts and unfractionated polyclonal antiserum were employed as test antigen and specific antibody respectively. Higher specificity was observed with the addition of gelatin and ovalbumin in the extraction medium and overnight incubation of ELISA plate at 5°C after substrate addition. Antigen titre was found to be very high in spear leaves followed by the next outer leaf. Similarly, maximum antigen titre was observed during the early stage of the diseased palm. The test could be completed within 44h and in a single ELISA plate, 20 samples with three replications could be screened using microlitre quantities of the specific antibody.